2014
DOI: 10.1051/epjconf/20147503002
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of Packed Co Nanorods for Hard Magnetic Applications

Abstract: Abstract. We present a numerical algorithm based on the bullet physics library to generate densely packed (39% -41%) structures of high-aspect-ratio nanorods for finite element micromagnetic simulations. The coercivities μ 0 H c of the corresponding Cobalt nanorod structures vary between 0.50T and 0.67T, depending on the overall orientation of nanorods, which is in good agreement with experimental results. The simulations make it possible to estimate the coercivity loss due to incoherent reversal processes (27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Calculations showed that for these two different diameters the magnetic reversal mode usually changes from vortex (for d=40 nm) to transverse DWs (for d=20 nm) [20,21]. The DW nucleation and reversal types have the most significant influence on the coercive field of NWs [20,21,34,35]. In our samples the difference in H c for NWs with two diameters is small (about 10%, cf.…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…Calculations showed that for these two different diameters the magnetic reversal mode usually changes from vortex (for d=40 nm) to transverse DWs (for d=20 nm) [20,21]. The DW nucleation and reversal types have the most significant influence on the coercive field of NWs [20,21,34,35]. In our samples the difference in H c for NWs with two diameters is small (about 10%, cf.…”
Section: Resultsmentioning
confidence: 58%
“…This large difference in the simulations is a consequence of the different mechanisms of magnetic reversal. Calculations showed that for these two different diameters the magnetic reversal mode usually changes from vortex (for d=40 nm) to transverse DWs (for d=20 nm) [20,21]. The DW nucleation and reversal types have the most significant influence on the coercive field of NWs [20,21,34,35].…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation